Pro Silverlight 4 in C# Create cross-platform .NET applications for the browser - MacDonald, Matthew. (Apress, 2010)
Silverlight 4 is Microsoft's cross-browser technology for creating rich user experiences on the Web. Like its predecessor, Silverlight 3, it rides atop the .NET framework for maximum ease of use and coding efficiency. The new technology carries forward much of the work that has been done before and augments it in many important respects, including support for H.264 video, major improvements to the graphics engine (including true 3D rendering), and much richer data-binding options for interfacing with other applications. Pro Silverlight 4 in C# is an invaluable reference for professional developers wanting to discover the features of Silverlight 4. Author Matthew MacDonald's expert advice guides you through creating rich media applications using Silverlight in the environment you're most productive inno matter what the target platform. As you learn about the features that put Silverlight in direct competition with Adobe Flash, such as rich support for 2D and 3D drawing, animations, and media playback, you'll experience the plumbing of .NET and the design model of WPF through Silverlightall of the same .NET technology that developers use to design next-generation Windows applications. Matthew MacDonald provides a comprehensive tutorial written from professional developer to professional developer, complete with full-color graphics and screenshots.